EEES, TIC and teaching planning: A practical approach in the Escuela de Ingeniería Informática in the ULPGC - Cuenca Hernández, Carmelo; Quintana Domínguez, Francisca (Historia y Comunicación Social, 2014)
This paper describes how to plan a course in the EEES framework, and how to put it into practice. In this context it is necessary to make a scheduling that includes both attending teaching hours and personal working hours, as well as a way to catch evidences of them, as all of them must contribute to the student’s evaluation. It also presents the results of the three years in which the course has been taught following the proposed planning. In general, the planning of the course has been well received by students who perceived that weekly effort is recognized and not played the course in a final exam. On average, over 88% of the students pass the subject with this planning.